Use the suggest account Equation to limited achieve level for Javelin throw - Jassim , Mohammed; Jawad , zaydoon (Journal of Physical Education, 2011)
The search included five sections, as it included the first section provided and the importance of research which was addressed to a general idea of the effectiveness of the Javelin throw and the importance of using the proposed equation to predict the improvement in the expectations of coaches . And contains the first door on one goal is to identify the difference distance between the fixed and mobile of the effectiveness of the Javelin throw, while the problem of the research focused on finding an equation predictive to determine the difference distance between the stand throw and throw from the movement, Part II included some of the main topics related to effectively discus throw, such as the stages of the technical performance of the effectiveness of the Javelin throw, While stated in Part III research methodology, as was the use of descriptive method and the sample was selected from the heroes of Araqi to the category of applicants specialists effectively the Javelin throw for the period 2011, was to extract the results of throw the moving from knowledge and fixed of stability through the application of the equation to predict proposed and compared the results with the results of the regression equation inhalers. Part IV guarantees the display, analyze and discuss the results of the data that was reached through the equations, the results showed high credibility of the equation with the equation proposed inhalers, While the conclusions emerged promised under section V, including the proposed equation gave accurate results for the achievement of the expected distance term, and a set of recommendations, including the researcher recommends using a predictive equation proposed to improve the expectations of coaches for their athletes.